2022
DOI: 10.21203/rs.3.rs-1380534/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study protocol for the Alzheimer and Music Therapy (ALMUTH) Study: a 12-month, Randomised Controlled Trial to Compare the Efficacy of Music Therapy and Physical Activity on Brain Plasticity, Depressive Symptoms, and Cognitive Decline, in a Population with and at Risk for Alzheimer’s Disease

Abstract: Background: There is anecdotal evidence for beneficial effects of music therapy in patients with Alzheimer’s Disease (AD). However, there is a lack of rigorous research investigating this issue. The aim of this study is to evaluate the effects of music therapy and physical activity on brain plasticity, mood, and cognition in a population with AD and at risk for AD.Methods: One-hundred and thirty-five participants with memory complaints will be recruited for a parallel, three-arm Randomized Controlled Trial (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Initially, the ALMUTH study was conducted exclusively in mild‐to‐moderate AD patients; however, a feasibility assessment and randomized pilot trial of the ALMUTH study found that the strict inclusion of AD patients was not feasible 82 . Therefore, milder forms of memory impairment have been included, namely, individuals with MCI, subjective cognitive decline (SCD), and subthreshold SCD 83 . The updated ALMUTH protocol taps into the longer preclinical AD phase by offering training across varying stages of memory impairment and seeks to uncover if enhancements in mood, activities of daily living, cognition, and brain plasticity as measured by neuroimaging methods (e.g., fiber tractography, voxel‐based morphometry, resting‐state functional connectivity, DTI structural connectivity, and BrainAGE) can reflect changes in the brain due to a musical or physical intervention.…”
Section: Alzheimer's and Music Therapy Studymentioning
confidence: 99%
“…Initially, the ALMUTH study was conducted exclusively in mild‐to‐moderate AD patients; however, a feasibility assessment and randomized pilot trial of the ALMUTH study found that the strict inclusion of AD patients was not feasible 82 . Therefore, milder forms of memory impairment have been included, namely, individuals with MCI, subjective cognitive decline (SCD), and subthreshold SCD 83 . The updated ALMUTH protocol taps into the longer preclinical AD phase by offering training across varying stages of memory impairment and seeks to uncover if enhancements in mood, activities of daily living, cognition, and brain plasticity as measured by neuroimaging methods (e.g., fiber tractography, voxel‐based morphometry, resting‐state functional connectivity, DTI structural connectivity, and BrainAGE) can reflect changes in the brain due to a musical or physical intervention.…”
Section: Alzheimer's and Music Therapy Studymentioning
confidence: 99%